(8) \( \frac{2 x+y}{x}=\frac{2 x}{x}+\frac{y}{x}=\square+\frac{y}{x} \) (9) \( \frac{a+b}{a}= \) (10) \( \frac{a^{2}+2 a+b}{a}= \) (11) \( \frac{a^{2}+a+1}{a}= \) (12) \( \frac{a^{3}-a^{2}+3 a}{a^{2}}= \) (13) \( \frac{x^{5}-3 x^{3}+6 x}{3 x^{2}}= \) (14) \( \frac{x^{2}-3 x-2}{2 x}= \) (15) \( \frac{x^{2}-2 x y+y^{2}}{2 x^{2} y}= \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Mind Expander
When we break down \( \frac{a+b}{a} \), it’s like asking how many times \( a \) fits into \( a + b \). Essentially, we can simplify it as \( 1 + \frac{b}{a} \), which gives us a clearer insight into the relationship between \( a \) and \( b \). Similarly, looking at \( \frac{a^2 + 2a + b}{a} \), we can separate it into manageable pieces: \( \frac{a^2}{a} + \frac{2a}{a} + \frac{b}{a} \). This becomes \( a + 2 + \frac{b}{a} \). It’s all about breaking down that complex fraction into digestible parts and understanding how every component works with respect to \( a \).